2020
DOI: 10.1186/s12876-020-01509-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive predictors of prognosis of Asian patients with histopathologically-confirmed lean nonalcoholic fatty liver disease

Abstract: Background The prognostic factors of morbidity and mortality in patients with lean NAFLD (body mass index < 25.0 kg/m2) are unknown. Methods In this retrospective study, 446 Japanese patients with histopathologically-confirmed NAFLD (lean NAFLD, n = 170) were followed for liver events, cardiovascular events, type 2 diabetes mellitus, and non-liver malignancies. The median observation period was 4.6 years. We also investigated the predictors of severe fibrosis (stage 3–4) and mortality in lean NAFLD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…There were 38 studies 43,45,46,59‐91,211,212 (40 cohorts; 2,361,275 participants) of cancer populations (Table S3); 17 cohorts were in East Asia, 10 cohorts in North America, 7 in Europe, 2 were international cohorts, 2 were in West Asia, and 1 each in South America and Africa. Mean age of participants ranged from 17 to 75 years.…”
Section: Resultsmentioning
confidence: 99%
“…There were 38 studies 43,45,46,59‐91,211,212 (40 cohorts; 2,361,275 participants) of cancer populations (Table S3); 17 cohorts were in East Asia, 10 cohorts in North America, 7 in Europe, 2 were international cohorts, 2 were in West Asia, and 1 each in South America and Africa. Mean age of participants ranged from 17 to 75 years.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that the incidence of advanced fibrosis and liver-related events in these patients is similar to or worse than that in patients with fatty liver who are overweight/obese. [51][52][53] In addition, a higher risk for ASCVD and higher all-cause mortality has been reported in patients with fatty liver in the context of normal weight than that in patients who are overweight/obese. [53][54][55] Patients with lean/normal weight fatty liver have been reported to progress to advanced liver disease, ASCVD, and liver-related mortality, independent of PNPLA3 genotype.…”
Section: Validity Of the Mafld Definition For People Who Are Lean/normal Weightmentioning
confidence: 99%
“…First, we excluded the Asian studies using the BMI cut-off by the WHO criteria. [22][23][24] Second, we systematically removed each study, one by one and analysed the results to verify if any single study had a significant impact on the overall findings. Subgroup analyses and sensitivity analyses were conducted exclusively when there were ≥4 eligible cohort studies, while meta-regressions were performed exclusively when there were ≥6 eligible cohort studies.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Ultimately, 8 studies were included in this systematic review and meta-analysis. 11,[22][23][24][26][27][28][29] The main characteristics of the 8 eligible cohort studies are summarized in Table S1. A total of 56 745 NAFLD individuals were included in the final analysis (31.2% were women; mean age 52.8 years; mean BMI 30.2 kg/m 2 ).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation